2013
DOI: 10.1088/1748-6041/8/2/025012
|View full text |Cite
|
Sign up to set email alerts
|

Targeted delivery of 10-hydroxycamptothecin to human breast cancers by cyclic RGD-modified lipid–polymer hybrid nanoparticles

Abstract: Lipid-polymer hybrid nanoparticles (NPs) combining the positive attributes of both liposomes and polymeric NPs are increasingly being considered as promising candidates to carry therapeutic agents safely and efficiently into targeted sites. Herein, a modified emulsification technique was developed and optimized for the targeting lipid-polymer hybrid NPs fabrication; the surface properties and stability of the hybrid NPs were systematically investigated, which confirmed that the hybrid NPs consisted of a poly (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 43 publications
(54 reference statements)
1
35
0
Order By: Relevance
“…In the present study, HCPT was demonstrated to effectively suppress cell viability, and to induce cytotoxicity and the apoptosis of human osteosarcoma MG-63 cells. Yang et al (15) suggested that HCPT suppressed the cell growth of human breast cancers, and further studies have demonstrated similar effects in murine melanoma pulmonary cancer (10) and lung cancer (16).…”
Section: Discussionmentioning
confidence: 91%
“…In the present study, HCPT was demonstrated to effectively suppress cell viability, and to induce cytotoxicity and the apoptosis of human osteosarcoma MG-63 cells. Yang et al (15) suggested that HCPT suppressed the cell growth of human breast cancers, and further studies have demonstrated similar effects in murine melanoma pulmonary cancer (10) and lung cancer (16).…”
Section: Discussionmentioning
confidence: 91%
“…4,5 For example, Arg-Gly-Asp (RGD) -or Asn-Gly-Arg (NGR)-modified targeting drug delivery systems have been extensively investigated. [6][7][8][9][10] [CRGDK/RGPD/EC]), has been reported to enhance vascularity and tissue permeability in a tumor-specific and neuropilin-1 (NRP-1)-dependent manner. 11 The mechanism for how iRGD homes to tumor sites has been explained in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have been reported for other lipid−PEG hybrid NP systems. 9,13,59 Analysis of pH-Responsive Swelling. To ensure that the lipid surface coating and modified preparation of the eNPs did not compromise their pH-responsive swelling, eNPs and PEG-L-eNPs were incubated in either pH 7.4 or pH 5 buffers for 24 h. Each batch was prepared to have a similar starting diameter of ∼350 nm as measured via qNano, since larger starting NP sizes enable easier detection and monitoring via the qNano.…”
Section: Biomacromoleculesmentioning
confidence: 99%